If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 80 + 9t = 7t Solving 80 + 9t = 7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7t' to each side of the equation. 80 + 9t + -7t = 7t + -7t Combine like terms: 9t + -7t = 2t 80 + 2t = 7t + -7t Combine like terms: 7t + -7t = 0 80 + 2t = 0 Add '-80' to each side of the equation. 80 + -80 + 2t = 0 + -80 Combine like terms: 80 + -80 = 0 0 + 2t = 0 + -80 2t = 0 + -80 Combine like terms: 0 + -80 = -80 2t = -80 Divide each side by '2'. t = -40 Simplifying t = -40
| 6y-2(5+3y)=15 | | -6x-2(5x-5)=-118 | | 3m-15=-5 | | 0.4x-x=49 | | 1.5x-7=11-1.5x | | -x^3+2x^2+x-2=0 | | (2x+6)=42 | | (6x^3-6x^2+2x)+(8x^3+9x^2-13x)= | | -5+4(2x+13)=16 | | 24+1.50m=3m | | 18x^2+9xy-20y^2=0 | | -9y-12=8-4y | | 3x+4=6x-8 | | 4x+7(-x+4)=13 | | 8-(3n-1)=5-4n | | (2r+6)/5=-4 | | y^3-7y^2+3y-21=0 | | 8=30 | | 2x-10=4x+30 | | 3x+5-7(x+1)=4x+3 | | 7h-4=12-3h | | -64=4x-2(-5x-10) | | (m-2)/9=3 | | -5v-10=-110 | | 1+8e-2e=22 | | 3=-1.5n | | 16d^2-14d-15=0 | | 2(6-x)=2x+6 | | 4(x)+10=38 | | 21-4h-13=37+13h | | 2x-6=6x-18 | | 2x-6(3x+2)=180 |